a+b=1,(6) => a+b = [tex] \frac{16-1}{9} [/tex] =[tex] \frac{15}{9} [/tex] dupa care simplificam prin 3 si ajungem la fractia [tex] \frac{5}{3} [/tex] ;
Prelucram si cealalta relatie :
a-b = 0, (3) = > a-b = [tex] \frac{3}{9} [/tex] , simplificam prin 3 , adica obtinem [tex] \frac{1}{3} [/tex] = >
=> a=b + [tex] \frac{1}{3} [/tex]
a+b = [tex] \frac{5}{3} [/tex]
b+[tex] \frac{1}{3} [/tex] + b =[tex] \frac{5}{3} [/tex]
2b=[tex] \frac{5}{3} [/tex]-[tex] \frac{1}{3} [/tex] = [tex] \frac{4}{3} [/tex] =>
=> 2b = [tex] \frac{4}{3} [/tex] => b = [tex] \frac{2}{3} [/tex]
a= b+[tex] \frac{2}{3} [/tex] = [tex] \frac{3}{3} [/tex]
Sper ca te-am ajutat ! :)